Economic Empowerment of Baitul Arqom Islamic Boarding: Building Innovative Synergies through the Triple Helix Approach - Hanifatirrosyidah, Umu; Rifa'i, Khamdan; Wadud, Abdul (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Islamic boarding schools have a great potential in developing the surrounding community's economy if they have an optimal synergize with supporting entities. This study reviews the economic development at Baitul Arqom Islamic boarding school based on the triple helix concept by Henry Etzkowitz and Loet Leydesdorff, which is an analytical model that explains the relationship between universities, industry/business, and government in economic development. This research aims to reveal the helix model and its implementation in building economic growth at Baitul Arqom Islamic Boarding School in Balung Jember. This research uses a qualitative descriptive research type and design with a case study research approach or strategy or CSR (Case Study Research). The informants (subjects) were selected using the purposive method. The informants for this research were Kiai, Islamic Boarding management, and the local community. The research results reveal that in terms of the triple helix, Baitul Arqom Islamic Boarding School can increase its innovation and economic development through synergy between universities, Islamic boarding schools/businesses, and the government in developing and maximizing its economic potential. Universities, industry, and government have worked well in developing curricula relevant to industry needs so that economic innovation in Baitul Arqom Islamic boarding school can be developed.